2002
DOI: 10.1097/00007632-200211010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-up of a Randomized Clinical Trial of Spinal Manipulation and Two Types of Exercise for Patients with Chronic Neck Pain

Abstract: The results of this study demonstrate an advantage of spinal manipulation combined with low-tech rehabilitative exercise and MedX rehabilitative exercise versus spinal manipulation alone over two years and are similar in magnitude to those observed after one-year follow-up. These results suggest that treatments including supervised rehabilitative exercise should be considered for chronic neck pain sufferers. Further studies are needed to examine the cost effectiveness of these therapies and how spinal manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
1
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 22 publications
4
95
1
9
Order By: Relevance
“…Ylinen et al [8,9] found that neck muscle training could increase strength of muscle and relieve the pain and enhance the activities of the patients' daily life. Additionally, studies indicated that combined program of strengthening and endurance exercises with manual therapy got a greater result in range of motion, and long-term pain relieve than manipulation only [10,11].Our results are similar to previous studies. Baduangong contribute to the physical function, for example, the movement of the extremities, especially the muscles around the shoulders.…”
Section: Disscusionsupporting
confidence: 90%
“…Ylinen et al [8,9] found that neck muscle training could increase strength of muscle and relieve the pain and enhance the activities of the patients' daily life. Additionally, studies indicated that combined program of strengthening and endurance exercises with manual therapy got a greater result in range of motion, and long-term pain relieve than manipulation only [10,11].Our results are similar to previous studies. Baduangong contribute to the physical function, for example, the movement of the extremities, especially the muscles around the shoulders.…”
Section: Disscusionsupporting
confidence: 90%
“…이중 경부의 장애는 나이와 성에 관계없이 매우 흔하게 나타나, 남성의 15%, 여성 의 23% 정도가 경험하게 되고, 많은 경우에서 만성통 증으로 이어질 수 있다. 특히 교통사고에 의한 경부 손상 환자가 더욱 증가하고 있는데 [3] , 이 경우 25~5 0%의 환자는 그 증상이 12개월 이상 지속된다고 보고 하였다 [4] . 기계적 경부통증(Mechanical neck pain)은 경부 움직 임(neck motion) 증가가 동반된 경흉추부의 통증으로 정의된다 [5] .…”
unclassified
“…The influence of techniques ameliorating the static and dynamic dysfunctions of the high levels of the cervical region proves the dominant role of the upper cervical spine in the generation of this type of back pain and headache [5][6][7]. We consider that the impact of the upper cervical region is determinant not only for the generation of the so called cervicogenic headache, but too -for the initiation and the aggravation of tension-type headache.…”
Section: Discussionmentioning
confidence: 99%